Electrocardiogram and heart rate variability assessment in patients with common autoimmune diseases: a methodological review - Soroor Behbahani; Farhad Shahram (KARE Publishing, 2020)
The aim of this article was to summarize current knowledge about the potential clinical utility of electrocardiogram (ECG) and heart rate variability (HRV) measures in patients with 4 common autoimmune diseases (ADs): rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), Behcet's disease (BD), and systemic sclerosis (SSc). A search was conducted of the PubMed, Embase, and Scopus databases using terms and a controlled vocabulary associated with these ADs, ECG, and HRV. The available, full-text articles published in English were considered. In all, 20 publications that examined the direct effect of these diseases on the heart were selected according to a systematic review protocol. Time-frequency domain analysis revealed that HRV parameters were lower in patients with the selected ADs in comparison with control groups. An increased QT dispersion and heart rate corrected QT, which are well-known as risk factors for sudden cardiac death, were observed in the patient group. In some studies, a correlation was seen between the duration of the disease and its activity, while others did not report such an association. Heart rate turbulence parameters were also examined. Turbulence onset was increased in SLE and SSc patients, while the turbulence slope was decreased in SLE patients. There was no significant change in these parameters in BD patients. Patients with ADs demonstrate abnormal HRV and ECG parameters, which indicates an autonomic cardiac functional impairment. Measurement of these parameters can be a useful clinical tool in the diagnosis and prediction of some disorders in patients with ADs. Both of these signals can provide helpful information for physicians to trace the efficacy of prescribed medicines.